EVALUATION OF ANTICANCER ACTIVITY OF ETHANOLIC EXTRACT OF CYPERUS KYLLINGIA ENDL. IN EHRLICH ASCITES CARCINOMA-INDUCED SWISS ALBINO MICE - Gangopadhyay, Amites; Chakraborty, Mainak; Haldar, Pallab Kanti; Chaulya, Nitai Chand; Ghosh, Amitava (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The purpose of the study was to evaluate the antitumor and antioxidant status of ethanolic extract of Cyperus kyllingia Endl. on Ehrlich ascites carcinoma (EAC)-treated mice. Methods: The determination of in vivo antitumor activity was performed using EAC cells inoculated mice groups (n=12). The groups were treated for 9 consecutive days with ethanolic extract of C. kyllingia (EECK) at the doses of 20 and 40 mg/kg b.w., respectively. After 24 h of the last dose, half of the mice were sacrificed and the rest were kept alive for assessment of increase in life span. The antitumor potential of EECK was assessed by evaluating tumor volume, viable and non-viable tumor cell count, tumor weight, hematological parameters, and biochemical estimations. Furthermore, antioxidant parameters were assayed by estimating liver tissue enzymes. Results: EECK showed direct cytotoxicity on EAC cell line in a dose-dependent manner. EECK exhibited significant (p<0.05) decrease in the tumor volume, viable cell count, tumor weight, and elevated the life span of EAC tumor-bearing mice. The hematological profile, biochemical estimations, and tissue antioxidant assay were reverted to normal level in EECK-treated mice. Conclusion: Experimental results revealed that EECK possesses potent antitumor and antioxidant properties. Further, research is going on to find out the active principle(s) of EECK for better understanding of mechanism of its antitumor and antioxidant activity.